THE IMPORTANCE OF MULTINATIONAL COMPANIES (MNCs) AND SMALL AND MEDIUM SIZED ENTERPRISES' (SMEs') INTERNATIONALIZATION AS BUSINESS DRIVERS IN GLOBALIZATION AND SLOWBALIZATION: MUTUAL SURVIVAL AND GROWTH FOR BUSINESS VALUES - Anis BENABED (Eastern European Journal of Regional Studies)
This paper analyzes, describes the possibilities of business internationalization for both MNCs and SMEs to survive from competition, risks, restrictions and market tights for business values. The results and analysis demonstrated that Small and Medium Sized Enterprises (SMEs) may use some models to internationalize their product, operations or services. Multinational companies (MNCs) that wish to leave markets tights should take into consideration the importance of location for them once they are determined that they have a strong ownership to compete with in foreign markets. Multinational companies may purchase SMEs in their locations to transform them to some of their subsidiaries and help them survive or merge them to their system. SMEs may grow by going for the internationalization process choosing the chosen suitable entry mode such as FDI in case the three conditions of the OLI model Ownership, location and internalization by Dunning (1988) are fulfilled. SMEs may merge with MNCs in their locations but they should not compete with them to avoid major losses. SMEs may follow the UPPSALA model (1977) and its four stages for their internationalization process. Furthermore, SMEs may choose any of the four Bartlett and Ghoshal’s strategies and typology for internationalization to become multinational, global, international or transnational if their internal and external budgets afford them for that. In conclusion, SMEs are considered driving companies for local economies in the EU and other economies with their rising numbers, they may remain domestic or grow through the process of export, import, outsourcing, licensing or franchising especially if they are innovative, they may follow the suitable internationalization entry mode in globalization. MNCs and SMEs are considered driving companies in globalization, according to this full paper and study both are drivers in globalization.